Fabrication of p-NiO/n-TiO2 Solar Device for Photovoltaic Application - R. T. Mouchou; K. O. Ukoba; O. T. Laseinde; T. C. Jen (International Journal of Photoenergy)
Energy demand is increasing globally owing to population growth. Solar cell development has gained considerable attention because of its potential to provide everyone with sustainable, affordable, clean, and globally accessible energy. A heterojunction solar device for photovoltaic applications was developed in this study, using nickel oxide (NiO) as the p-type and titanium oxide (TiO2) as the n-type. The material chosen was motivated by the affordability, availability, and performance compared to existing silicon that is more efficient but less affordable and available. The TiO2 and NiO2 were synthesised and characterised before the deposition and characterisation of the solar cells. The characterisation was carried out using Fourier transform infrared spectroscopy (FTIR), Transmission Electron Microscopy (TEM), scanning electron microscopy (SEM), EDX, X-ray Diffraction (XRD), and a four-point probe. The deposition parameters were fine-tuned to achieve optimum optoelectronic properties for the solar device. The final device exhibited an open-circuit voltage of 370 mV, a current density of 1.7 mA, and solar cells efficiency of 3.7.